2017
DOI: 10.1007/s41465-017-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Meditation is Effective in Reducing Sleepiness and Improving Sustained Attention Following Acute Sleep Restriction

Abstract: Optimal information processing requires appropriate mobilization of mental resources. Sleep loss increases homeostatic sleep pressure, thereby reducing mobilization of mental resources and consequently diminishing attention function. Meditation techniques engage attention processes and mobilize mental resources needed to sustain control of these processes, suggesting a promising role for meditation in counteracting attention deficits associated with sleep loss. Following a 21-day training period with a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…As further support for this hypothesis, meditation has also been shown to alleviate cognitive decline associated with sleep-deprivation (Chatterjee et al, 2012(Chatterjee et al, , 2018Kaul et al, 2010;Kohler et al, 2017).…”
Section: Could Meditation Improve Cognition Through Sleep?mentioning
confidence: 88%
“…As further support for this hypothesis, meditation has also been shown to alleviate cognitive decline associated with sleep-deprivation (Chatterjee et al, 2012(Chatterjee et al, , 2018Kaul et al, 2010;Kohler et al, 2017).…”
Section: Could Meditation Improve Cognition Through Sleep?mentioning
confidence: 88%
“…To take a more rigorous analytical approach to coherence and power, we applied phase synchronization to analyze functional connectivity during meditation. Other phase locking methods have found increased gamma (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) coherence during rest and during loving kindness meditation (19), increased theta coherence during open monitoring Vipassana meditation (20), and increased alpha coherence during TM (5).…”
Section: Specifically Transcendental Meditation (Tm) Practitioners Ha...mentioning
confidence: 99%
“…Throughout the varied histories of meditation traditions there have been fantastic claims and benefits that their training can bring, along with more modest claims, such as increased emotional regulation, stress reduction, improved attentional performance, and increased lifespan (11,20,(31)(32)(33)(34)(35)(36). This study aims to determine the short-term impact of meditation on physiological attention in novices.…”
Section: Specifically Transcendental Meditation (Tm) Practitioners Ha...mentioning
confidence: 99%
See 1 more Smart Citation
“…The data showed that the degree to which participants improved their understanding of themselves predicted their improvements in understanding others' mental states, namely, theory of mind (TOM) performance. Kohler et al (2017) investigated the effects of a concentrative form of yoga nidra meditation on attention performance in a sample of ten young healthy participants before and after restricted sleep and again after a session of meditation or rest. Following meditation, but not rest, sustained attention improved and sleepiness decreased, a finding that could indicate a role for meditation in improving attention deficits associated with sleep loss.…”
mentioning
confidence: 99%